2013
DOI: 10.12809/hkmj133909
|View full text |Cite
|
Sign up to set email alerts
|

Severity of airflow limitation, co-morbidities and management of chronic obstructive pulmonary disease patients acutely admitted to hospital

Abstract: Objective To assess the disease spectrum, severity of airflow limitation, admission pattern, co-morbidities, and management of patients admitted for acute exacerbations of chronic obstructive pulmonary disease. Design Case series.Setting An acute regional hospital in Hong Kong.Patients Adult subjects admitted during January 2010 to December 2010 with the principal discharge diagnosis of chronic obstructive pulmonary disease. ResultsIn all, the records of 253 patients with physician-diagnosed chronic obstructiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 13 publications
2
16
0
1
Order By: Relevance
“… 16 Scattered reports on the prevalence of COPD comorbidities in HK have been published, but data from large-scale studies are lacking. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“… 16 Scattered reports on the prevalence of COPD comorbidities in HK have been published, but data from large-scale studies are lacking. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…The relationship between COPD exacerbation and the degree of airflow limitation was demonstrated by several studies …”
Section: Severe Airflow Limitationmentioning
confidence: 96%
“…64 A study developed in Hong Kong showed that 77% of hospital admissions were for patients with COPD with moderate to severe airflow limitation. 65 Montes de Oca et al revealed an increased number of medical visits directly correlated with the airflow obstruction severity and dyspnea, 66 while Foda showed that an increased airway obstruction determined a more severe AECOPD. 67…”
Section: Limitationmentioning
confidence: 99%
See 2 more Smart Citations